Implementasi Kurikulum Merdeka Belajar Di Sekolah Dasar - Yulia Ruti Cahyanti; Upita Ayu Widayanti; Zafida Rohmawati Khusna; Istianah Khoiriah; Dina Celline Megasari; Sri Suwartini (CV. ITTC INDONESIA, 2024)
When viewed from the facts on the ground, the implementation of the Independent Curriculum (IKM) shows that it has not been fully realized due to various problems, including at the elementary school level. Therefore, it is important to carry out an evaluation, starting with identifying obstacles so that appropriate solutions are determined. This research aims to identify obstacles and solutions in implementing the Independent Curriculum at the elementary school level. This research is a literature study that uses the Systematic Review (SR) method or better known as Systematic Literature Review (SLR). The research results show that obstacles in SMEs come from four aspects, namely 1) related to facilities and infrastructure; 2) human resources for teachers and teaching staff, 3) conditions of students, families and the environment; 4) inequality in government policies. The solution assistance for these challenges is 1) maximizing funding from the government; 2) teachers actively participate in training (workshops) related to SMEs; 3) achieving good cooperation among all school members, and; 4) implement policies according to the Independent Curriculum if there is an imbalance in government policies.